Community Satisfaction on Health Services in Maternal and Child Health Units of Simolawang Public Health Center - Adi Pamungkas, Sista Prasetyo (Health Notions, 2018)
One of the efforts to be made in improving public services is to conduct a community satisfaction survey to service users. As the types of public services vary widely with different traits and characteristics, a community satisfaction survey can use appropriate survey methods and techniques. The purpose of this study was the satisfaction of the public on health services at maternal and child health unit Unit of Simolawang Community Health Center. This research used descriptive survey method. The study was conducted in April 2015 at the Maternal and Child Health Unit of Simolawang Community Health Center. The sample amounted to 50 respondents selected at random sampling. Data collected in this activity was primary data obtained through interviews. The completed questionnaires were then collected and processed quantitatively. From the results of the assessment of service satisfaction, it was found that service time was the lowest satisfaction element that was 2.94 but overall from nine elements of service from maternal and child health unit Unit of Simolawang Community Health Center has the value of Public Satisfaction Index (IKM) that was 74.20 which means the value of service quality of Simolawang Public Health Center Surabaya was Good. Public health center should prioritize service quality improvement on service speed indicator by speeding up service waiting time. Keywords: Satisfactions, Health care center, Community, Health service